Prototypes of dosage forms for prolonged release of antioxidants on the basis of a silica-gelatine matrix and orchids extracts - Ivannikov, R.V.; Laguta, I.V.; Stavinskaya, O.N.; Kazakova, O.O.; Buyun, L.I. (Reports of the National Academy of Sciences of Ukraine, 2019)
Bioactive extracts from the leaves of the plants of Orchidaceae Juss. are prepared, and antioxidant properties of the extracts are investigated. Gelatine and silica-gelatine films with incorporated antioxidants molecules are obtained using the extracts as bioactive ingredients. The swelling of the films in the aqueous medium and the desorption of the bioactive compounds into water are studied. The inclusion of the extracts in both gelatine and silica-gelatine films are found not to affect the films properties, while the presence of silica in the films leaded to a significant retardation of the swelling of films and to a deceleration of the antioxidants desorption. Thus, the silica-gelatine films with embedded orchid extracts seem to be promising dosage forms for the prolonged antioxidants release: the components of the extracts are effective natural antioxidants, while the silica-gelatine matrix provides their gradual release and prolonged action.